Hubungan Status Gizi Dengan Kemampuan Motorik Halus Anak Usia 2-3 Tahun - Dwi Yanti (2018)
Children 24-36 months of age at the time, the growth and development at this time in particular continuous improvement nervous system. In order for growth and development is not hampered, one way is by providing adequate and balanced nutrition. But in this era of globalization is mostly found children suffering from malnutrition that led to the development and growth is not in accordance with his age. Populations and samples in this study were children aged 2-3 years in the Village IHC Sawahan Nganjuk Together with the number of 30 children were taken to the cross-sectional technique. Data collection tools used in this research is the primary data source of data on nutritional status by weighing, and using questionnaires on KPSP. The results showed most of the children with good nutrition as much as 17 respondents (56.66%) and the majority of the child's development in accordance with the number of 18 respondents (60%). This shows that p <α then Ho is rejected and Ha accepted the correlation coefficient between nutrition and the development of .689 is signifikan.Hal shows that nutritional status There anara relationship with the fine motor skills in children aged 2-3 years IHC Village Together Sawahan Nganjuk in 2013